Incentives for international environmental cooperation: Theoretic models and economic instruments - Carsten Schmidt (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper surveys the rapidly growing theoretical literature on international environmental agreements. The surveyed contributions are classified according to the conceivable strategies to create incentives for the participation in and compliance with environmental conventions. The proposed taxonomy of instruments consists of (i) the choice and particular form of the internalisation instrument; (ii) carrot-stick strategies that make co-operative pollution reductions dependent on the past behaviour of other countries (internal stabilization); (iii) transfers and sanctions of various forms (external stabilization); (iv) unilateral and accompanying measures by single countries or subcoalitions; and (v) long-term provisions to increase the flexibility of agreements and to improve the framework conditions for international negotiations.
Keywords: D62; D7; F02; H21; Q28; 330; International environmental agreements; Co-operation; Transboundary environmental externalities; Incentive compatibility; Enforcement; Umweltabkommen; Internationale Zusammenarbeit; Externer Effekt; Ökonomischer Anreiz; Theorie